2007
DOI: 10.1002/ange.200603681
|View full text |Cite
|
Sign up to set email alerts
|

Auflösung von Amyloidaggregaten durch einen kontrolliert induzierten Übergang von einer β‐Faltblatt‐ in eine α‐Helix‐Struktur: eine Anwendung des Schalterkonzepts

Abstract: Manche Probleme lösen sich auf: Die Rückführung einer vom Amyloid abgeleiteten β‐Faltblatt‐ in eine lösliche α‐Helix‐Struktur durch Anwendung eines Schaltelements S (siehe Schema, σ ist eine helixinduzierende Einheit) kann wesentlich zum Verständnis der Fibrillogenese beitragen, die als molekulare Ursache degenerativer Erkrankungen wie der Alzheimer‐ oder der Parkinson‐Krankheit gilt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…[69] More recently, they designed a switch peptide that disrupts amyloid-like b-sheet assemblies by converting the peptides into a-helices. [70] Koksch et al synthesized peptide VW19 (LKVELKELK-KELVVLKSELKELKKEL) that contains structural elements matching both a-helical folding and b-sheet formation. Depending on the environmental conditions (pH and/or concentration of the peptide), it can assume a random-coil, bsheet, or coiled-coil conformation.…”
Section: Switch Peptidesmentioning
confidence: 99%
“…[69] More recently, they designed a switch peptide that disrupts amyloid-like b-sheet assemblies by converting the peptides into a-helices. [70] Koksch et al synthesized peptide VW19 (LKVELKELK-KELVVLKSELKELKKEL) that contains structural elements matching both a-helical folding and b-sheet formation. Depending on the environmental conditions (pH and/or concentration of the peptide), it can assume a random-coil, bsheet, or coiled-coil conformation.…”
Section: Switch Peptidesmentioning
confidence: 99%
“…Moreover, they can help to elucidate the molecular interactions that occur during structural transition and the formation of amyloid fibrils, and more importantly they can provide insights into different strategies for inhibiting amyloid formation. [41][42][43] We recently designed and synthesized a series of 26-residue model peptides that were based on the characteristic heptad repeat of the a-helical coiled-coil motif. By incorporating valine residues at three different solvent-exposed positions, the system was made more prone to amyloid formation.…”
Section: Introductionmentioning
confidence: 99%
“…For LC-MS, an analytical Vydac C4 column (Grace Vydac, 4.6 250 mm, 5 mm particle size, flow 1 mL min ) was employed, with the same buffer system as used for LC-MS. Milli-Q water with a resistance of more than 18.2 MW cm À1 was provided by a Millipore Milli-Q filtering system with filtration through a 0.22 mm Millipak filter. 1 H NMR and 13 C NMR spectra were measured with a Bruker AC-200 (200 and 50.1 MHz, respectively). Chemical shifts are reported in ppm downfield from internal tetramethylsilane (0.00 ppm).…”
Section: Experimental Section General Materials and Methodsmentioning
confidence: 99%
“…It has been shown that predefined transitions can be designed a priori, for instance, solution-to-gel, nematicto-isotropic phase, and random-coil-to-b-sheet transitions. [1] These findings have offered a way to generate discrete and smart nanostructures of b-sheet peptides, which is an important step in the production of functional materials. [2] Many scientists have studied the ability of b-sheet-forming amphiphilic peptides to self-assemble into several structures.…”
Section: Introductionmentioning
confidence: 98%